2004
DOI: 10.1002/hec.887
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the health of populations: the veil of ignorance approach

Abstract: We report the results from two surveys designed to explore whether an application of Harsanyi's principle of choice form behind a veil of ignorance (VEI) can be used in order to measure the health of populations. This approach was tentatively recommended by Murray et al. (Bull. World Health Organ 2000; 78 : 981-994; Summary Measures of population health: Concepts, Ethics, Measurement and Applications, WHO, 2002.) as an appropriate way of constructing summary measures of population health (SMPH) for comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Although these methods may refer to a probabilistic framework that is different from ours (depending on the specific interpretation of the questions involved), the same basic problem is present with the use of a veil-of-ignorance-based index as quality-adjustment factor in a QALY model (or disability weight in a DALY model). An interesting recent experiment [34] has, however, indicated that a veil-of-ignorance-based index is closer to an individual quality-adjustment factor than a person trade-off based index, which therefore in this respect reduces the practical importance of a potential conflict with the Pareto principle.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although these methods may refer to a probabilistic framework that is different from ours (depending on the specific interpretation of the questions involved), the same basic problem is present with the use of a veil-of-ignorance-based index as quality-adjustment factor in a QALY model (or disability weight in a DALY model). An interesting recent experiment [34] has, however, indicated that a veil-of-ignorance-based index is closer to an individual quality-adjustment factor than a person trade-off based index, which therefore in this respect reduces the practical importance of a potential conflict with the Pareto principle.…”
Section: Discussionmentioning
confidence: 94%
“…Procedures related to person trade-off called veil-ofignorance methods have also recently drawn some attention (e.g., [23,30,34]). Although these methods may refer to a probabilistic framework that is different from ours (depending on the specific interpretation of the questions involved), the same basic problem is present with the use of a veil-of-ignorance-based index as quality-adjustment factor in a QALY model (or disability weight in a DALY model).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on these initial results, research on the sources of bias in eliciting utility functions has been particularly eminent in the 1980s (e.g., Tversky and Kahneman 1981;Hershey et al 1982;Hershey and Schoemaker 1985;de Neufville 1984, 1986;Johnson and Schkade 1989;Schoemaker and Hershey 1992), but this topic also plays a major role in more recent research (e.g., Starmer 2000;Loubergé and Outreville 2001;Abdellaoui et al 2005;Maule and Villejoubert 2007). In particular, there have been several studies in the domain of health-related decisions, which investigate inconsistencies in utility elicitation (e.g., Bleichrodt et al 2001;Oliver 2003;Pinto-Prades and Abellán-Perpiñán 2005;Bleichrodt et al 2007). …”
Section: Theoretical Background and Hypothesesmentioning
confidence: 97%
“…11 Wolfson described this as the necessary differentiation between the size of the pie and the manner in which the pie is divided (page 175). 15 Nord, 16 and Pinto-Prades and Abellan-Perpinan 17 are counter examples to this trend, and have touched on the legitimacy of the separation-but tangentially. They considered people's preferences for two populations with different mixes of health states.…”
mentioning
confidence: 99%